Pemanfaatan Biokoagulan Gambas Kering sebagai Pengolahan Limbah Cair Batik - Novirina Hendrasarie; Raden Kokoh Haryo Putro; Farhan Athallah Ajiputra (Prosiding ESEC, 2022)
Batik wastewater comes from the dyeing process of batik fabrics. Reactive dyestuffs are synthetic dyes that are often used. Reactive dyes that are often used are Methyl Orange (MO) and Methyl Blue. Only 5% of the dyestuffs are used in batik dyeing, the remaining 95% will be discarded. The content of dyestuffs used causes batik liquid waste to have alkaline, cardiogenic properties, difficult to decompose and contain high organic substances. So that batik wastewater treatment is needed before it is discharged into water bodies, coagulation is one of the waste treatment methods that can be used. The purpose of this study is to determine the decrease in pollutant parameters in the form of TSS and color by the biocoagulant of dried luffa cylindrica. This study was conducted by varying the dose of coagulants and pH of coagulants with a stirring speed of 200 rpm for 2 minutes and a stirring speed in the flocculation process of 60 rpm with a time of 40 minutes. The highest removal of color content and Total Suspendid Solid (TSS) occurred in the use of biocoagulant at a dose of 3500 mg / l pH 6, namely 76% and 75% respectively.